TNFRSF10A downregulation induces retinal pigment epithelium degeneration during the pathogenesis of age-related macular degeneration and central serous chorioretinopathy. Issue 13 (1st February 2022) - Mori, Kenichiro; Ishikawa, Keijiro; Fukuda, Yosuke; Ji, Rui; Wada, Iori; Kubo, Yuki; Akiyama, Masato; Notomi, Shoji; Murakami, Yusuke; Nakao, Shintaro; Arakawa, Satoshi; Shiose, Satomi; et al.
Abstract: Age-related macular degeneration (AMD) and central serous chorioretinopathy (CSC) are common diseases that can cause vision loss in older and younger populations. These diseases share pathophysiological conditions derived from retinal pigment epithelium (RPE) dysfunction. Tumor necrosis factor receptor superfamily 10A (TNFRSF10A)-LOC389641 with the same lead single-nucleotide polymorphism (SNP) (rs13278062) is the only overlapped susceptibility locus found in both AMD and CSC through genome-wide association studies. This lead SNP has been reported to alter the transcriptional activity of TNFRSF10A . This study aimed to elucidate the function of TNFRSF10A in RPE degeneration using human primary RPE cells and Tnfrsf10 knockout ( Tnfrsf10 −/− ) mice. TNFRSF10A was found to be localized in human RPE. In vitro assays revealed that a T allele of rs13278062, the risk allele for AMD and CSC, downregulated TNFRSF10A transcription in RPE, leading to decreased cell viability and increased apoptosis through protein kinase C-α ( PKCA ) downregulation. Treatment with phorbol 12-myristate 13-acetate, a PKC activator, rescued the cell viability. Morphological RPE abnormality was found in the retina of Tnfrsf10 −/− mice. Our data suggest that downregulation of TNFRSF10A expression inactivates PKCA signaling and causes cellular vulnerability of the RPE, which may contribute to the pathogenesis of AMD and CSC.